(Re)imagining an archive of haunting. (February 2023) - Hach, Maria
This creative non-fiction piece explores my research and writing practice as it relates to my research on intergenerational haunting among women of the Cambodian diaspora. It describes my process towards capturing affective traces of the past, and my attempts to (re)imagine an archive of haunting.